PENINGKATAN RESPON IMUN IKAN NILA (Oreochromis niloticus) DENGAN PEMBERIAN EKSTRAK DAUN Macaranga tanarius - Saparuddin Saparuddin; Edi Ilimu (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
The problem of tilapia farming farmers is the presence of disease, which is caused by viruses, bacteria, fungi, and parasites. Prevention by farmers is the provision of vaccines, antibiotics, and immunostimulants. However, it is only effective in one type of disease. Therefore, alternative prevention is needed with natural ingredients from Macaranga tanarius leaf extract which has tannins, terpenoids, flavonoids, prenylflavonoids, and lignans that have immunostimulator properties. M. tanarius leaf extract was injected by intramuscular injection of tilapia. This research method used a completely randomized design (CRD) with five treatments with three repetitions. Treatment (P1) using physiological solution (positive control), P2 = 4 % (v/v) (1mL extract + 24 mL distilled water), P3 = 8 % (v/v) (2mL extract + 23 mL distilled water), P4 = 12% (v/v) (3mL extract + 22 mL distilled water) and P5 without injection of M. tanarius leaf extract (negative control). The results showed that the leaf extract of M. tanarius could respond to phagocytic activity (45.82%) and increase the number of white blood cells (12.43 x 108 cells/mL). Based on this study, the extract of M. tanarius showed an increase in the immune response of tilapia.